2017
DOI: 10.1016/j.bbmt.2017.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Increased Foxp3 + Helios + Regulatory T Cells and Decreased Acute Graft-versus-Host Disease after Allogeneic Bone Marrow Transplantation in Patients Receiving Sirolimus and RGI-2001, an Activator of Invariant Natural Killer T Cells

Abstract: Regulatory T (Treg) cells play a central role in immune tolerance and prevention of aberrant immune responses. Several studies have suggested that the risk of GVHD after allogeneic hematopoietic cell transplantation (HCT) can be ameliorated by increasing Tregs. We have developed an approach of in vivo expansion of Tregs with RGI-2001, a novel liposomal formulation of a synthetic derivative of alpha-galactosylceramide, a naturally occurring ligand that binds to CD1 and activates and expands invariant natural ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…While encouraging, fecal transplantation is still to be considered a highly experimental treatment approach and needs validation in carefully designed prospective clinical trials. Other approaches currently being explored to prevent or treat GVHD in patients are blockade of T-cell co-stimulation 101 , α-GalCer, a glycolipid that expands and activates natural killer T cells and subsequently expands Treg in patients 102 , anti-inflammatory antibodies, proteins or drugs targeting signaling by IL-6 103 , IL-23 104 , or multiple cytokine signaling pathways using HDAC inhibitors 105 , proteosomal inhibition 106 , or the anti-inflammatory protease inhibitor, alpha-1-antitrypsin 107 . Additionally, Janus-activated kinase (JAK)-1/2 inhibitors have shown promising results in preclinical studies 108,109 as well as in retrospective clinical analyses 110 and are currently being tested in prospective randomized studies.…”
Section: Novel Acute Gvhd Preventive and Therapeutic Strategies Beingmentioning
confidence: 99%
“…While encouraging, fecal transplantation is still to be considered a highly experimental treatment approach and needs validation in carefully designed prospective clinical trials. Other approaches currently being explored to prevent or treat GVHD in patients are blockade of T-cell co-stimulation 101 , α-GalCer, a glycolipid that expands and activates natural killer T cells and subsequently expands Treg in patients 102 , anti-inflammatory antibodies, proteins or drugs targeting signaling by IL-6 103 , IL-23 104 , or multiple cytokine signaling pathways using HDAC inhibitors 105 , proteosomal inhibition 106 , or the anti-inflammatory protease inhibitor, alpha-1-antitrypsin 107 . Additionally, Janus-activated kinase (JAK)-1/2 inhibitors have shown promising results in preclinical studies 108,109 as well as in retrospective clinical analyses 110 and are currently being tested in prospective randomized studies.…”
Section: Novel Acute Gvhd Preventive and Therapeutic Strategies Beingmentioning
confidence: 99%
“…Thus, we presumed that transferred donor CD8 + T cells worked as “veto” cells. It is known that murine iNKT cells usually do not include CD8 + fraction . The engraftment was also shown when donor iNKT cells were deleted from BMCs before transfer (Figure S5).…”
Section: Discussionmentioning
confidence: 90%
“…Allogeneic T‐cell transfer is also conducted in clinical experiments examining the induction of mixed chimerism and has been shown to yield greater engraftment in preliminary results . In the recently published report of multicenter phase I/II clinical trial (NCT01379209) investigating lipo‐αGC in patients undergoing myeloablative allogeneic HSC transplantation showed the safety and efficacy of this concept . Thus, we expect that iNKT therapy combined with allogeneic T‐cell transfer may be feasible for facilitating BM engraftment without increasing the risk of GvHD and could result in establishment of stable complete chimerism in non‐myeloablative recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional immunomodulatory therapies have also been shown to affect Treg cell numbers in GvHD besides IL‐2. One study suggested that in vivo expansion of Treg cells may occur upon administration of a novel liposomal formulation of a synthetic derivative of alpha‐galactosyl‐ceramide, a surrogate ligand that binds to CD1d and activates NKT cells (Duramad et al , ; Chen et al , ). Patients received this drug on day 0 of allogeneic HSCT, and the incidence of GvHD was lower among patients who responded to this drug.…”
Section: Indirect Measures To Activate Treg Cells In Gvhd Patientsmentioning
confidence: 99%